PENERAPAN MODEL PEMBELAJARAN THINK TALK WRITE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVD SD NEGERI 136 PEKANBARU - Siska Maisari; Lazim N Lazim N; Guslinda Guslinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Problem in this is the low student learning outcomes IPS IVD grade publik school students 136 Pekanbaru, with an average of 64,88 and 40,47% in the classical comple teness minimum completeness criteria (KKM) which is set by the scool is 70. This research in the form of classroom action research (CAR), which aims to the improve learning outcomes IPS graders domestic IVD SD 136 Pekanbaru. The application of learning models think talk write (TTW) once applied learning models think talk write (TTW) increased student learning outcomes at UH 1with an average of 74,28 with the increase of the basic score 14,48% with classical completeness is 73,81% (not finis hed). And the average UH II is 82,26. With the increase of the basic score 26,78% with classical completeness 90,47% (complete). While the average percentage of activity the teachers in the first cycle of the first meeting is 69,44% in both categories and increased by 2,78% in the second meeting to 72,22% in both categories, the second cycle of the first meeting of the percentageof the average teacher activity increased by 8,38% to 80,6% in both categories and the second meeting increases by 5,51% to 86,11%. With the category very well, besides the activity of students in the first cycle of the first meeting with the average percentage is 63,8% in both categories increased by 8,42%, the second meeting to 72,22% in both categories, the second cycle of the first meeting of the average percentage of student activity increased by 11,11% to 83,33% in both categories once and the second meeting is increased by 2,78% to 86,11% with the category very well,based on the results of these studies it can be concluded that the application of learning models think talk write (TTW) can improve learning outcomes IPS IVD grade public school students 136 Pekanbaru.Key Words : Think Talk Write (TTW), Learning Outcomes IPS.